Effect of Roller Mill Processed Fenugreek Fiber Addition on Rheological and Bread Making Properties of Wheat Flour Doughs. Issue 4 (4th August 2016) - Sakhare, Suresh D.; Prabhasankar, P.
Abstract: Effect of rolled milled fenugreek fiber (FF) addition on rheological and bread making properties of wheat flour doughs were studied. Farinograph water absorption increased from 58.5 to 89.6% and dough stability (5.2–10.3 min) with increase in amount of FF from 0 to 20%. Decrease in pasting temperature, increase in peak viscosity, hot paste viscosity, cold paste viscosity with increase in FF. Bread volume significantly decreased from 561 to 356 mL and crumb firmness value increased with increase in FF. Overall quality score decreased from 89.3 to 66.2 for the maximum score of 100 with the addition of 10% FF. Addition above this level significantly reduced the overall quality score. Replacement of 10% FF was found to be acceptable by sensory evaluation and further improved by addition combination of additives (CA). Volume increased from 447 to 555 and crumb firmness value decreased showing improvement in the bread crumb texture. Practical Application: Fenugreek fibers are known for their hypoglycaemic and hypocholesterolemic effect. Incorporation of the roller milled fenugreek fiber fraction in the bread increases the total dietary fiber content including soluble and insoluble fiber content of the bread. Bread fortified with fenugreek fiber can be used for the diabetic patients. Hence, the developed product is invaluable in the bread industries.